BLACK FEMINISM IDEAS AS PORTRAYED IN HOMAGE TO MY HIPS POEM BY LUCILLE CLIFTON - Indra Maulana; Ely Nurmaily (English Department, STKIP PGRI Bandar Lampung, 2021)
This research discusses a poem written by Lucille Clifton entitled homage to my hips. The researchers aim to describe the portrayal of black feminism ideas inside the poem to raise awareness regarding the issues of discrimination toward the black community especially women. This study aims to answer the question of how is the black feminism ideas portrayed in the poem entitled homage to my hips by Lucille Clifton. This research used descriptive qualitative method typically library research with textual analysis since the data of this research are in the form of words and phrases within the stanza. The data source is the poem entitled Homage to My Hips poem by Lucille Clifton, and data sources are the poet’s background of life, journals, and previous studies. This research used intersectionality and black feminism thought theory as the approaches. In order to answer the research question, the researchers used the parameters of black feminism ideas according to the black feminist thought and intersectionality theory to capture the ideas of black feminism in the poem. The results of this research show that the poem entitled homage to my hips by Lucille Clifton is portrayed the ideas of black feminism, which strongly ignores and rejects the continuous approaches of the oppression system both in practice and the ideas that justify it, based on the parameters that cover the existence of black feminism according to the black feminist thought and intersectionality approaches.